Perceived patient benefits from using prescription opioids and other therapies to manage persistent pain - Mitra, MD, MBBS, FRACGP, DA, Dip. AC, Farzana; Woolley, PhD, MPHTM, Torres (Journal of Opioid Management, 2020)
Objective: There is current controversy surrounding the long-term prescription of opioids to persistent pain (PP) patients due to potential dangers of addiction and overdose. This study is the first to explore the perspectives of PP patients attending a multidisciplinary pain clinic on the benefits associated with using opioids and other self-medication strategies for pain relief. Design, patients, and setting: Cross-sectional study utilizing a self-administered survey of patients attending an Australian General Practice pain clinic for treatment of PP for at least 1 year (n = 93; response rate = 89 percent). Results: Of the 93 participants, 79 percent reported being on opioid medication, with 49 percent on such medication for over 1 year. One or more side-effects were experienced by 53 percent of PP patients using opioids (although all felt these side-effects were at least “somewhat” acceptable). In addition, 64 percent of PP on opioid medication felt the benefits were “substantially” worth the risk of harm, and 50 percent reported their medication had led to “substantial” improvements in their quality of life. Many PP patients also used nonprescription medications and other complementary therapies for pain relief; however, only the illicit drug cannabis was consistently stated (by 79 percent of users) to have benefits regarding relaxation and sleeping. Conclusion: Overall, PP patients felt the benefits of opioid use outweighed the risks, and using opioid medication significantly improved their quality of life. This may be partly due to the poor efficacy of other nonprescription medications and complementary therapies in managing PP beyond short-term relief.